Electrical and Thermal Stability of ALD-Deposited TiN Transition Metal Nitride Schottky Gates for AlGaN/GaN HEMTs. (2nd June 2016) - Shahin, David I.; Anderson, Travis J.; Wheeler, Virginia D.; Tadjer, Marko J.; Koehler, Andrew D.; Hobart, Karl D.; Eddy, Charles R.; Kub, Francis J.; Christou, Aris
Abstract : TiN, a transition metal nitride, has been evaluated as an electrically and thermally stable Schottky gate material for AlGaN/GaN high electron mobility transistors. HEMTs with 75 nm TiN gates deposited via atomic layer deposition at 350°C exhibited improved static and dynamic on-state characteristics compared to Ni/Au-gated HEMTs. Reverse bias gate stressing indicated a higher critical voltage and higher breakdown voltage for the TiN-gated HEMTs. The TiN gated devices exhibited stable DC operation after annealing at temperatures as high as 800°C, while the Ni/Au gates exhibited significant degradation after annealing above 500°C and failed catastrophically at 800°C.